Sauvignon blanc Cultivar Aroma - A Review - Marais, J. (South African Journal of Enology and Viticulture, 2017)
The typical cultivar aroma of Sauvignon blanc may be described as containing vegetative, grassy, herbaceous, gooseberry, asparagus and green pepper nuances. The chemical components responsible for these aromas are reviewed. The most important components are methoxypyrazines, especially 2-methoxy-3-isobutylpyrazine. Other components, such as 4-methyl-4-mercapto-pentan-2-one, monoterpenes, C13-norisoprenoids, C6-alcohols and C6-aldehydes may also contribute to the complexity of Sauvignon blanc aroma. Factors affecting methoxypyrazine levels and therefore the typical Sauvignon blanc cultivar aroma are, amongst others, origin/climate and level of grape ripeness. Methoxypyrazine concentrations decrease with grape ripening and under increased sunlight and temperature conditions. To produce Sauvignon blanc wines with typical aromas, vines should be cultivated in cool areas and wines stored in dark rooms to retain these aromas.